2012
DOI: 10.11609/jott.o3032.2928-32
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hairs of some mammalian prey of large cats in Gir Protected Area, India

Abstract: for the necessary lab facilities. The help of Dr. Vimal Bhuva in taking microphotographs is also acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…The scale margin was rippled in Sambar, crenate in Nilgai and smooth in Spotted deer. Similar cuticular scale margin was observed by Dharaiya and Soni (2012).…”
Section: Results a N D Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The scale margin was rippled in Sambar, crenate in Nilgai and smooth in Spotted deer. Similar cuticular scale margin was observed by Dharaiya and Soni (2012).…”
Section: Results a N D Discussionsupporting
confidence: 86%
“…1b). Dharaiya and Soni (2012) noted similar cuticular scale pattern in Sambar, Nilgai and Spotted deer. Bhat et al (2014) also observed irregular wave cuticular scale pattern in Nilgai with close distance between scale margins.…”
Section: Results a N D Discussionsupporting
confidence: 52%
“…Such analysis provides less morphological information for species identification than hair cross sections. For the publications in which cross-sectioning of mammalian hair was performed, the quality of sections was in agreement with our results for handsectioning (39,(49)(50)(51). Unfortunately, the method used for crosssectioning mammalian hairs was not described in these studies.…”
Section: Resultssupporting
confidence: 86%
“…(Andheria et al 2007;Avinandan et al 2008;Upadhyaya et al 2018). The comparative analyses of the different morphological approaches (cuticular, medullary and cross-section) for prey identification confirmed the efficacy of the medullary approach over the others (Dharaiya and Soni 2012;Souza and Azevedo 2020) (Supplementary data SD3, Supplementary data SD4). Given that the Indian subcontinent currently retains the largest tiger population across the range residing within the most varied habitat types (Jhala et al 2020(Jhala et al , 2021, such information will be of great importance towards habitat management and conflict mitigation.…”
Section: Discussionmentioning
confidence: 67%